Effectiveness of more strict managements after achievement of standard target value of low-density lipoprotein cholesterol in secondary prevention of Japanese patients. (25th November 2020) - Endo, A; Kagawa, Y; Sato, H; Morita, Y; Kawahara, H; Yasuda, Y; Ouchi, T; Watanabe, N; Yamaguchi, K; Yoshitomi, H; Tanabe, K
Abstract: Background: In secondary prevention of coronary artery disease, target value of low-density lipoprotein cholesterol (LDL-C) <100 mg/dL is recommended as standard management in Japanese guideline. The guideline also stated that strict management of LDL-C targeting <70 mg/dL is considered in some high risk patients. However, in Japanese patients, effectiveness of more strict management of LDL-C lowering therapy for prevention of long-term cardiovascular events remains unclear. Purpose: The purpose of the present study was to evaluate whether the strict management of LDL-C targeting <70 mg/dL was effective to prevent recurrence of long-term coronary events than standard management in patients with previous percutaneous coronary intervention (PCI). Methods: We investigated 344 patients with previous PCI who underwent late coronary angiography to examine recurrence of cardiac ischemia beyond the early phase of restenosis from January 2007 to August 2019. Patients were stratified into three groups according to achieved LDL-C value; LDL-C <70mg/dL (n=53), 70 to <100mg/dL (n=130) and ≥100mg/dL (n=161). Endpoints of this study were recurrence of cardiac ischemia presenting as acute coronary syndrome (recurrence-ACS) and any late coronary revascularization. Results: During average 7.1 years follow-up, 200 patients (58%) underwent any late coronary revascularization. In 94 of those patients, recurrence-ACS was observed. The incidence of recurrence-ACS was significantly lower in patients with achieved LDL-C <70mg/dL than in those with LDL-C 70 to <100mg/dL and LDL-C ≥100mg/dL (p=0.009 and p=0.001, respectively), however, there was no difference between patients with LDL-C 70 to <100mg/dL and LDL-C ≥100mg/dL (p=0.140). Any late revascularization was significantly lower in patients with achieved LDL-C <70mg/dL and in those with LDL-C 70 to <100mg/dL than in those with LDL-C ≥100mg/dL (p=0.002 and p<0.001, respectively), however, no difference was found between patients with LDL-C <70mg/dL and LDL-C 70 to <100mg/dL (p=0.119). Moreover, in patients with achieved LDL-C <100mg/dL (n=183), multivariate analysis identified that LDL-C (HR 1.035, p=0.007) and HbA1c (HR 1.338, p=0.001) were independent predictors of recurrence-ACS. In contrast, only using statins (HR 0.461, p=0.009) was an independent predictor of recurrence-ACS in patients with achieved LDL-C ≥100mg/dL. Conclusions: LDL-C was the important residual risk of recurrence-ACS even after recommended standard LDL-C lowering management had been achieved. More strict management of LDL-C targeting to <70mg/dL should be considered to prevent recurrence-ACS for wider range of Japanese patients in secondary prevention. Funding Acknowledgement: Type of funding source: None